Reducing Degrees of Freedom in Surgical Suturing: Implications for Minimally Invasive Device Development—A Prospective Experimental Study. Issue 4 (August 2021) - Wilhelm, Peter; Lambidis, Lisa; Williams, Jacob; Axt, Steffen; Storz, Pirmin; Kunert, Wolfgang; Kirschniak, Andreas; Rolinger, Jens
Abstract : Open surgery allows the use of all 6 degrees of freedom (DOF; x - y - z and roll-pitch-yaw), whereas laparoscopy requires working under limitation to 4 axes. We present a prospective experimental study evaluating translational and rotational DOF restriction in surgical suturing tasks. An experimental platform included a kinematic structure that limited the maneuverability of the surgical instruments. The subjects (n=20) worked in a randomized order using (1) 6DOF, (2) 4DOF with 3 translational and 1 rotational DOF (4TRANS), and (3) 4DOF with 1 translational and 3 rotational DOF (4ROT). The time required to perform each task was recorded. Suturing and knot tying were significantly faster under 6DOF compared with 4ROT (both P <0.001) and 4TRANS (both P <0.001). Assessment of subjective difficulty and impairment showed most favorable results for 6DOF. The advantage of rotational compared with translational DOF should be considered in the development of future surgical devices.